2022
DOI: 10.23969/biosfer.v7i1.5463
|View full text |Cite
|
Sign up to set email alerts
|

ETNOBOTANI MASYARAKAT SUKU LIO: STUDI KASUS di DESA WATURAKA KAWASAN TAMAN NASIONAL KELIMUTU KABUPATEN ENDE NUSA TENGGARA TIMUR

Abstract: Potensi tumbuhan obat yang terdapat di Taman Nasional Kelimutu belumdimanfaatkan secara optimal oleh masyarakat di sekitarnya. Tumbuhan obat tradisional ini biasanya digunakan oleh dukun dan diwariskan turun temurun secara lisan dan menggunakan nama lokal. Hal ini mengakibatkan hilangnya informasi akan tumbuhan obat tersebut pada generasi selanjutnya. Tujuan dari penelitian ini adalah untuk mengetahui interaksi masyarakat sekitar dengan keanekaragaman tumbuhan di kawasan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, the number of medicinal plants in the study sites is lower than that of Lambung Mangkurat Education Forests (South Kalimantan, 56 species) [15] and Kelimutu National Park (East Nusa Tenggara, 47 species) [16]. Variation in the number of medicinal plants is highly affected by climatic and geographical conditions, forest type, and local wisdom [14,16]. The lower number of medicinal plants at the study site (compared to other regions) might also be related to the small size of the research station and management intervention to introduce 11 species of trees for research purposes [10].…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…However, the number of medicinal plants in the study sites is lower than that of Lambung Mangkurat Education Forests (South Kalimantan, 56 species) [15] and Kelimutu National Park (East Nusa Tenggara, 47 species) [16]. Variation in the number of medicinal plants is highly affected by climatic and geographical conditions, forest type, and local wisdom [14,16]. The lower number of medicinal plants at the study site (compared to other regions) might also be related to the small size of the research station and management intervention to introduce 11 species of trees for research purposes [10].…”
Section: Resultsmentioning
confidence: 77%
“…The number of medicinal plants in Inamberi Research station is almost equal to Martelu Purba Nature Reserve in North Sumatra Province (44 species) [11], and higher than other locations such as the Special Purpose Forest Area (Kawasan Hutan Dengan Tujuan Khusus, KHDTK) of Samboja (37 species) [12], and KHDTK UM Palangkaraya (30 species) [13], and KHDTK Rantau (South Kalimantan, 16 species) [14]. However, the number of medicinal plants in the study sites is lower than that of Lambung Mangkurat Education Forests (South Kalimantan, 56 species) [15] and Kelimutu National Park (East Nusa Tenggara, 47 species) [16]. Variation in the number of medicinal plants is highly affected by climatic and geographical conditions, forest type, and local wisdom [14,16].…”
Section: Resultsmentioning
confidence: 99%
“…The data is then compiled into teaching materials which include common names, regional names, scientific names, taxonomy, morphology, content and utilization and then developed into website-based learning media. Daud & Manu, 2021;Demita et al, 2021;Elfrida et al, 2021;Gunarti et al, 2021;Gunawan et al, 2022;Haba et al, 2022;Huda et al, 2022;Jamun et al, 2020;Kissinger et al, 2021;Leksikowati et al, 2020;Maharani et al, 2021;Manurung et al, 2016;Nasution et al, 2021;Ngineikon et al, 2022;Qasrin et al, 2020;Rahmawati & Hidajati, 2017;Ricky et al, 2019;Risnawati & Nurhayatina, 2022;Kemenkes, 2015;Rizki et al, 2019;Rupilu & Watuguly, 2018;Slamet & Andarias, 2018;Sulastri et al, 2021;Suryatinah et al, 2020;Tabeo et al, 2019;Taek et al, 2018;Tima et al, 2020;Wae et al, 2022;Wijana & Rahmawati, 2020;Yansip et Then, instructional analysis is based on the competencies expected in the Kurikulum Merdeka, namely that students are expected to have competencies related to internal factors (identity, ideology, and ideals of Indonesia) and external factors (industrial revolution), namely becoming superior and productive citizens in this Century 21 st . These factors are formulated into six key dimensions, one of which is critical reasoning.…”
Section: Resultsmentioning
confidence: 99%
“…Other folk medicine studies within the Lio community have focused on documenting Sua Soza, a healing mantra in the Ende language (Bala and Hua 2020), and the documentation of the Tu Gelu healing ritual, which involves the treatment of mystical ailments through the mediation of a traditional healer, involving the exchange of items representing livestock (Wula and Mboka 2021). Additionally, ethnobotanical studies recording the plant species utilized by the Lio people for traditional healing have shown that there are 47 plant species in the village of Waturaka and 52 plant species in the village of Detuwulu in Ende Regency used for traditional healing (Wae, Gago, and Ngapa 2022;Deda 2019).…”
Section: Introductionmentioning
confidence: 99%